Effects of Alpinia oxyphylla stems and leaves extracts on immune function, antioxidant function, and microbial flora composition in the intestinal tract of Jiaji ducks - Wang, Yongliang; Chen, Zhe; Peng, Weiqi; Hu, Chengjun; Wu, Hongzhi; Lyu, Renlong; Tan, Bie; Xu, Tieshan; Ji, Fengjie (Frontiers in Veterinary Science, 2025)
Alpiniae Oxyphyllae (A. oxyphylla) has been widely used as a traditional herbal medicine, and our previous studies have shown that its extracts from stems and leaves have a beneficial role in Jiaji ducks health. This study aimed to further investigate the effects of the Alpinia oxyphylla stems and leaves extracts (AOE) on the intestinal health of fattening Jiaji ducks. Four hundred and eighty 42-day-old Jiaji ducks were randomly allocated and equally divided into four treatment groups. The control group (CK) was fed a basal diet, and the AOE groups (groups Y1, Y2 and Y3) were fed with supplement 30, 80, or 130 mg/kg of AOE diets for 49 days. The results showed that the stems and leaves of A. oxyphylla contain abundant anti-inflammatory and antioxidant compounds, such as fatty acyls, terpenoids, flavonoids, and phenols. Compared with the CK group, the AOE groups (Y1, Y2, and Y3) exhibited significant effects in the immune and antioxidant functions. Among them, the mRNA expression of interleukin-10 (IL-10), heme oxidase-1 (HO-1) and nuclear factor E2-related factor 2 (Nrf2) in jejunal mucosa was significantly up-regulated (p = 0.005, p = 0.007, p = 0.005) in the AOE groups (Y1, Y2, and Y3). The levels of lysozyme, intestinal alkaline phosphatase (AKP), glutathione peroxidase (GSH-Px) and anti-superoxide anion radical (ASA) were markedly increased (p < 0.05) in jejunal mucosa of the Y1 groups. Moreover, the Spearman analysis demonstrated that the microbial biomarkers Ruminiclostridium_9 were positively correlated (p < 0.05) with HO-1 and Nrf2 in jejunal mucosa, and Bacteroidales were positively correlated (p < 0.05) with lysozyme activity. In contrast, Lachnospiraceae_unclassified and Firmicutes_unclassified were negatively correlated (p < 0.05) with lysozyme activity. In conclusion, dietary supplementation with 30 mg/kg of AOE is the most suitable dose to maintain the healthy homeostasis of the intestinal tract of Jiaji ducks, which can inhibit intestinal inflammatory responses, improve antioxidant function and alter the composition of intestinal microorganisms.